2004
DOI: 10.1039/b403226h
|View full text |Cite
|
Sign up to set email alerts
|

Theory and numerical simulation of droplet dynamics in complex flows—a review

Abstract: We review theoretical and numerical studies and methods for droplet deformation, breakup and coalescence in flows relevant to the design of micro channels for droplet generation and manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
221
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(228 citation statements)
references
References 110 publications
3
221
0
1
Order By: Relevance
“…When shear stress overcomes surface tension, the extended aqueous bolus breaks off and quickly relaxes to a spherical geometry as it passes downstream 23 . Figure 1b shows the aqueous bolus at the T-junction with three droplets in succession moving quickly towards the channel center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When shear stress overcomes surface tension, the extended aqueous bolus breaks off and quickly relaxes to a spherical geometry as it passes downstream 23 . Figure 1b shows the aqueous bolus at the T-junction with three droplets in succession moving quickly towards the channel center.…”
Section: Resultsmentioning
confidence: 99%
“…Droplet size was estimated from the computed volumetric flow rates, channel hydraulic diameter, carrier fluid viscosity, and surface tension. 23 These analyses indicated that a channel width of 60 μm at the T-junction was optimal for generating 10-picoliter droplets. As seen in Figure 1a, downstream from the droplet generation zone, the channel expands to bring more droplets into the optical field of view, allowing more droplets to be observed while stopped on-chip.…”
Section: Methodsmentioning
confidence: 97%
“…1,[9][10][11] These include level set methods, 12 phase field methods, 13,14 marker methods, 15 and VOF methods, [16][17][18] combined with spatial and temporal discretizations such as the boundary integral formulation, 19 finite elements, and finite differences. [20][21][22] A phase field method was developed in Ref.…”
Section: Numerical Algorithmmentioning
confidence: 99%
“…This allows for the generation of monodisperse emulsions by moving droplets through networks of microchannels. 1 For example, droplets of controllable sizes can be produced when two immiscible fluids flow through a T-junction channel. 2 Despite the recent research focus on droplet-based microfluidic techniques, open questions still remain for the understanding of drop deformation and breakup in a T-junction.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet size is adjusted by varying channel geometry, flow rate, and dispersed phase viscosity 10,11 . An effective T-junction width for channels of rectangular cross section was determined previously 9 and has been applied to the circular cross section used in this study.…”
Section: Methodsmentioning
confidence: 99%